Cost-utility analysis of rhTSH for differentiated thyroid carcinoma from a societal perspective - Millan Fachi, Mariana; de Fátima Bonetti, Aline; Andrade Oliveira, Layssa; Alves Oliveira Junior, Haliton; Camila Lucchetta, Rosa (JORNAL DE ASSISTÊNCIA FARMACÊUTICA E FARMACOECONOMIA, 2025)
Objective: The treatment of individuals with differentiated thyroid carcinoma (DTC) includes thyroidectomy followed by radioiodine (¹³¹I) ablation. For treatment effective-ness, elevated TSH levels are essential, which can be achieved through thyroid hormone withdrawal for 4-6 weeks after thyroidectomy. However, considering the limitations of withdrawal, the use of recombinant human TSH (rhTSH) could be an alternative. This study aims to evaluate whether rhTSH is cost-effective compared to the induction of en-dogenous hypothyroidism (IHE) by levothyroxine withdrawal, from the societal perspec-tive. Methods: A cost-utility analysis was conducted following the Brazilian Ministry of Health’s guidelines, using a Markov model with four health states (pre-ablation, ablation, post-ablation, and recovered). A 17-week time horizon (weekly cycles) was adopted from the societal perspective, including direct and indirect costs. Effectiveness was measured in quality-adjusted life years (QALYs). Probabilistic and deterministic sensitivity analy-ses were also performed. Results: The results showed that rhTSH treatment provides greater clinical benefit (0.2687 vs. 0.2602 QALYs) at an incremental cost (R$ 4,762 vs. R$ 4,135), with an incremental cost-utility ratio (ICUR) of R$ 73,662/QALY gained. The most impactful factors were the cost of rhTSH, lost workdays, and utility values. Conclusion: The findings suggest that rhTSH offers greater clinical benefits, spite of additional costs and could be a cost-effective alternative depending on the willingness-to--pay threshold for society’s perspective. Brazil did not recommend a willingness-to-pay threshold for this perspective and if it coincided with the threshold adopted for the SUS, rhTSH would be cost-effective for a threshold of R$120,000/QALY gained.